Toward An Integration of the Behavioral and Cognitive Influences on the Entrepreneurship Process. (11th September 2015) - Pryor, Christopher; Webb, Justin W.; Ireland, R. Duane; Ketchen, Jr., David J.
Abstract : Research summary: Entrepreneurs develop innovations, fulfill customer needs, and spur economic growth by recognizing, evaluating, and exploiting opportunities. Despite progress, scholarly understanding of how entrepreneurs achieve these objectives may be incomplete. For instance, little explanation exists for why entrepreneurs may pursue activities seemingly at random, nor is there a clear endpoint to the entrepreneurship process. To address these concerns, we present a framework that integrates sensemaking and structuration perspectives to specify the cognitive and behavioral influences on the entrepreneurship process. Within this framework, entrepreneurs ultimately pursue opportunities through developing and deploying capabilities to create value for customers. Managerial summary: While entrepreneurs' initial insights regarding innovations and customer needs are important, these insights are only the beginning of an interactive, iterative path that ends with the formation of an organization that can reliably produce value for customers. One of entrepreneurs' most important tools along this path is their set of scripts. Scripts help define how entrepreneurs act and interact so they can fully understand market needs and develop the means for solving these needs. In this paper, our objective is to describe how these scripts help entrepreneurs do the hard work of thinking and acting to effectively create new venture capabilities and to explain how entrepreneurs, who may possess similar sets of scripts, may nevertheless conceptualize different opportunities and solutions.